SakKijâjuk: Art and Craft from Nunatsiavut - Igloliorte, Heather; Broomfield, Jenna Joyce; Chaulk, Aimee; Lalonde, Christine; Pottle, Barry (Goose Lane Editions, 2017)
Nunatsiavut, the Inuit region of Canada that achieved self-government in 2005, produces art that is distinct within the world of Canadian and circumpolar Inuit art. The world's most southerly population of Inuit, the coastal people of Nunatsiavut have always lived both above and below the tree line, and Inuit artists and craftspeople from "Nunatsiavut have had access to a diverse range of Arctic and Subarctic flora and fauna, from which they have produced a stunningly diverse range of work. Artists from the territory have traditionally used stone and woods for carving; fur, hide, and sealskin for wearable art; and saltwater seagrass for basketry, as well as wool, metal, cloth, beads, and paper. In recent decades, they have produced work in a variety of contemporary art media, including painting, drawing, printmaking, photography, video, and ceramics, while also working with traditional materials in new and unexpected ways. SakKijâjuk: Art and Craft from Nunatsiavut is the first major publication on the art of the Labrador Inuit. Designed to accompany a major touring exhibition organized by The Rooms Provincial Art Gallery of St. John's, the book will feature more than 80 reproductions of work by 45 different artists, profiles of the featured artists, and a major essay on the art of Nunatsiavut by Heather Igloliorte. SakKijâjuk - "to be visible" in the Nunatsiavut dialect of Inuktitut - provides an opportunity for readers, collectors, art historians, and art aficionados from the South and the North will come into intimate contact with the distinctive, innovative, and always breathtaking work of the contemporary Inuit artists and craftspeople of Nunatsiavut
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé